Education of persons with disabilities: own experiences. Authoetnography - Lejzerowicz, Magda; Boryca, Wiktoria; Podstawka, Katarzyna; Salska, Paulina; Sanecka, Aleksandra; Surgiel, Paulina; Westfal-Kuczyńska, Anna; Wróblewska, Monika (Disability and education, 2023)
The aim of the research is a change in research competency of participants, getting methodology knowledge, ability of using it in practise and reflection on their own experiences in education of people with disabilities.Using autobiography elements authors reveal their reflections on education experiences. Working on the article allowed authors to change their approach to scientific research, getting to know autoethnographic method and a change in perception of the described social reality. All article’s authors are researchers, as well as the ones who were examined.